PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM, DAN PENGANGGURAN TERHADAP KETIMPANGAN PENDAPATAN JAWA TIMUR - PUTRI, RIZKA NOVITA; HANIFA, NURUL (Universitas Negeri Surabaya, 2024)
Income inequality is one of the most discussed problems in the world. The purpose of this study is to examine the effect of the following variables on income inequality: economic growth, minimum wage, and unemployment rate from 2019-2023 in East Java Province. Using quantitative methodology and Eviews 10 software, the data used is secondary data from the Central Bureau of Statistics. Specifically, this research finds that minimum wage and economic growth both significantly affect this inequality, while the unemployment rate has no such impact. These three variables all affect income inequality in East Java Province at the same time.